Tanfīdh Faṣl al-Munāẓarah fī (Nāfilah) li Tarqiyyati Mahārah al-Kalām - Hikmah Rahmasari; Alis Asikin; Dwi Mawanti (Alsina : Journal of Arabic Studies, 2020)
This paper searches for the implementation of the debate chapter in (Nafila) to upgrade the speech skills of students of Walisongo State Islamic University Semarang 2019/2018. The background of this research is the lack of good proficiency for students in the Arabic language, especially in the skill of speaking when debating. Nafilah is a member of the Student Activities Union at Walisongo State Islamic University Semarang, who helps her to preserve the Arabic language at the University. The definition of the question in this research is how to implement the debate chapter in (Nafilah) to upgrade the speech skill of students of Walisongo State Islamic University Semarang, especially in the debate class. What are the driving and resistance factors in it? This research is qualitative and descriptive research, and it is carried out at the Walisongo State Islamic University Semarang. The researcher uses interview, observation, and documentation as her data collection methods. As for the data analysis method, it is by triangulating data, sources, and the method. The result of the research is: Nafilah uses the communicative method to achieve a special purpose, which is to upgrade the speech skills of students when debating. Learning to debate in the debate class has two stages. They are the discussion phase and the debate phase. And the implementation of the debate chapter superfluous systems of the Asian Parliament The factors driving and hindering the implementation of this debate chapter are in terms of the conditions of the students, the trainer, and the supervisor.